Light Trapping in Ultrathin Monocrystalline Silicon Solar Cells. Issue 11 (3rd July 2013) - Yu, Ki Jun; Gao, Li; Park, Jae Suk; Lee, Yu Ri; Corcoran, Christopher J.; Nuzzo, Ralph G.; Chanda, Debashis; Rogers, John A.
<x xml:space="preserve">Abstract</x> Light‐trapping schemes implemented with ultrathin, 3 μm thick silicon solar cells offer excellent opportunities for greatly enhanced absorption and corresponding improvements in efficiency of operation. Optically optimized cells of this type yield energy conversion efficiencies that are higher by ≈190% compared to otherwise identical cells that do not exploit light‐trapping features, consistent with optical modeling results. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>